The Role of Wetlands for Climate Change Mitigation and Biodiversity Conservation - T.T. Dinsa; D.O. Gemeda (Journal of Applied Sciences and Environmental Management)
Wetland is crucial in supporting biodiversity conservation and climate change regulation. A wetland ecosystem has been influenced by anthropogenic driven climate change. The main objective of this paper is to analyze the role of wetlands for climate change mitigation and biodiversity conservation through literature review. Wetland is vulnerable to climate change through alterations of hydrological regimes that lead to changes in quantity and quality of water. Climate change is undoubtedly the most pervasive, complex and challenging of the global environmental issues facing contemporary society and it affects all aspects of development. Wetlands play a key role in hydrological and biogeochemical cycles, and provide a wide range of ecosystem goods and services to humankind. In spite of these facts, wetlands are considered as wastelands in the past, which contributes for deterioration of wetlands in several places. Thus, strong environmental policy is required for the conservation of wetland ecosystem.